Determinants of burnout among the employees of Gweru City Council - Musvovi, Gilbert (Midlands State University, 2017)
The study was about Determinants of Burnout among the Employees of Gweru City Council Participants were 50 employees (m= 35; f= 15) who were identified and recruited through stratified random sampling. The Maslach Burnout Inventory was adopted for use in the study.Data was analysed using descriptive statistics (i.e., frequencies and percentages). Results revealed that burnout among employees of Gweru City Council emanated from work overload, interpersonal conflict, role conflict and management style. It was recommended that the employees must be given the opportunity to make decisions on the way the work should be organised. Changes are supposed to be implemented in a way that all the employees understand the reason for the change. Conflicts are supposed to be handled in fair manner. Employees must be given time off that will enable them to have time to rest. Job descriptions should be given to all the employees so that they understand their roles.